(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Populationsof seven speciesof AlliumL. were studied in the Mykolayiv Region with evaluating. vitality of individuals and quality and vitality type of coenopopulations. It is revealed, that negative changes in vitality structure of populationare caused by strengthening of human activity impact.